2015
DOI: 10.1080/00036846.2015.1071474
|View full text |Cite
|
Sign up to set email alerts
|

Parity reversion in the Asian real exchange rates: new evidence from the local-persistent model

Abstract: This article investigates the time-series properties of 13 Asian real exchange rates (RERs) vis-à-vis the US dollar. The half-life point estimates drawn from the local-persistent model are all less than 2 years, with a finite upper bound. There is no evidence to indicate that the Asian financial crisis has altered the speed of the purchasing power parity (PPP) adjustments. We find that the persistence of RERs over the last three decades remains unchanged in majority of the cases. Given the fairly rapid speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Box plot of the fitted residuals 10 Maican and Sweeney (2013) who considered several specifications found that the linear model is superior to the nonlinear specification and may help to explain the PPP puzzle. Our work seems to support their view in the sense that the PPP puzzle is not an issue in the countries under review; see Baharumshah et al (2015). In most of the Asian countries, large swings occurred in currency markets during the AFC.…”
Section: Data and Empirical Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Box plot of the fitted residuals 10 Maican and Sweeney (2013) who considered several specifications found that the linear model is superior to the nonlinear specification and may help to explain the PPP puzzle. Our work seems to support their view in the sense that the PPP puzzle is not an issue in the countries under review; see Baharumshah et al (2015). In most of the Asian countries, large swings occurred in currency markets during the AFC.…”
Section: Data and Empirical Resultssupporting
confidence: 76%
“…on the type of testing models and outcome of unit-root tests (Zhou & Kutan, 2011). It should be mentioned here that the speed of adjustment to PPP tends to be faster during crisis (uncertainty) periods as proven in Baharumshah et al (2015). Specifically, we observed that the speed of convergence vis-à-vis the dollar (as measured by the half-life estimates) is faster for the post-crisis period; see also Ozdemir and Cakan (2010) on similar issue.…”
Section: Literature Reviewsupporting
confidence: 65%
See 2 more Smart Citations
“…We formally test (ˆn Q ) the null (Table 3) show that all of the d are significantly different from zero. As in Kim and Lima (2010) and Baharumshah et al (2015), we find strong support of the locally persistent process in the RER. Table 4 summarizes the proportion of upper-bound estimates of half-lives for three time intervals (less than 6 months, from 6-12 months, and more than 12 months) for 11 CEE countries, EU-5, and EU-16 (11 CEE plus EU-5) countries.…”
Section: Half-lifementioning
confidence: 60%